Neighborhood‐Level Drinking Norms and Alcohol Intervention Outcomes in HIV Patients Who Are Heavy Drinkers. (20th August 2016) - Elliott, Jennifer C.; Delker, Erin; Wall, Melanie M.; Feng, Tianshu; Aharonovich, Efrat; Tracy, Melissa; Galea, Sandro; Ahern, Jennifer; Sarvet, Aaron L.; Hasin, Deborah S.
Abstract : Background: Heavy alcohol consumption can be harmful, particularly for individuals with HIV. There is substantial variability in response to interventions that aim to reduce drinking. Neighborhood drinking norms may explain some of this variability among HIV‐infected patients. Therefore, we investigated whether neighborhood‐level drinking norms modified response to alcohol intervention among HIV‐infected heavy drinkers. Methods: Heavily‐drinking HIV comprehensive care patients ( n  = 230) completed 1 of 3 brief alcohol interventions (an educational intervention, a motivational interviewing [MI] intervention, or an MI intervention with a technological enhancement called HealthCall). Drinking was reported at baseline and end of treatment (60 days). Neighborhood‐level drinking norms were obtained from a separate general population study. Results: Patients' reductions in drinks per drinking day in response to MI (as compared with the educational control) were more pronounced in neighborhoods with more permissive drinking norms. In contrast, patients' reductions in drinks per drinking day in response to MI plus HealthCall did not significantly vary between neighborhoods with different drinking norms. Norms did not evidence significant interactions with intervention condition for 3 other exploratory drinking outcomes (drinking frequency, binge frequency, and maximum quantity). Conclusions: Neighborhood‐level drinking norms help explain differential response to an alcohol MI intervention among HIV‐infected patients. This study suggests the utility of considering neighborhood context as an effect modifier of alcohol interventions. Abstract : Using a sample of HIV‐infected heavy drinkers, this study evaluated whether effects of two alcohol interventions (Motivational Interviewing [MI] alone or supplemented with an interactive technological enhancement called Healthcall) varied according to acceptability of drinking in participants' neighborhoods. Results suggested that the efficacy of MI alone differed according to neighborhood norms, with MI alone only demonstrating effects in more permissive neighborhoods. The efficacy of MI + HealthCall did not vary by neighborhood, suggesting more robust effects of this intervention on drinking reduction. Intervention effects at selected levels of neighborhood unacceptability of drinking: Illustration of significant interaction between neighborhood drinking norm and intervention condition on drinks per drinking day.